Imaging Cannabinoid Receptors: A Brief Collection of Covalent and Fluorescent Probes for CB1 and CB2 Receptors - Hamilton, A.J.; Payne, Alan; Mocerino, Mauro; Gunosewoyo, Hendra (CSIRO PUBLISHING, 2021)
There has been an expanding public interest towards the notion that modulation of the sophisticated endocannabinoid system can lead to various therapeutic benefits that are yet to be fully explored. In recent years, the drug discovery paradigm in this field has been largely based on the development of selective CB2 receptor agonists, avoiding the unwanted CB1 receptor-mediated psychoactive side effects. Mechanistically, target engagement studies are crucial for confirming the ligand-receptor interaction and the subsequent biological cascades that lead to the observed therapeutic effects. Concurrently, imaging techniques for visualisation of cannabinoid receptors are increasingly reported in the literature. Small molecule imaging tools ranging from phytocannabinoids such as tetrahydrocannabinol (THC) and cannabidiol (CBD) to the endocannabinoids as well as the purely synthetic cannabimimetics, have been explored to date with varying degrees of success. This Review will cover currently known photoactivatable, electrophilic, and fluorescent ligands for both the CB1 and CB2 receptors. Structural insights from techniques such as ligand-assisted protein structure (LAPS) and the discovery of novel allosteric modulators are significant additions for better understanding of the endocannabinoid system. There has also been a plethora of fluorescent conjugates that have been assessed for their binding to cannabinoid receptors as well as their potential for cellular imaging. More recently, bifunctional probes containing either fluorophores or electrophilic tags are becoming more prevalent in the literature. Collectively, these molecular tools are invaluable in demonstrating target engagement within the human endocannabinoid system.